Improving the fuel economy and reduction of pollutants from Automobiles using HHO gas - A.L.R.Prathyusha, Dr.T Nancharaiah, (International Journal of Scientific Research and Management (IJSRM), 2015)
The consumption of fossil fuels spawns environmental considerations in addition to issues of energy demand, national security and resource availability. At global level, scientists warn that the combustion of fossil fuels is significantly changing the world’s climate system. So help the fossil fuels to exist longer life in turn to help survive this in ever automobile industry. In order to overcome the draw backs of the fossil fuels it is the time to completely or partially replace this fuel. So an innovative idea to overcome these problems is the HHO gas. HHO gas is also known as brown gas produced from splitting water into hydrogen and oxygen from electrolysis and allowing the gas to stay in a premixed state for use on demand without the need of storage. This project work describes about implementing the HHO fuel in diesel engine and comparing the fuel consumption of normal fuel (diesel) to secondary fuel (HHO) and showing the reduction of carbon emissions from the vehicles using this HHO fuel. Also the performance of the engine is also tested under normal diesel and diesel with HHO. Based on the experimental results the advantages of diesel with HHo over normal diesel are reported.